2020
DOI: 10.1007/s00345-020-03440-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined radiotherapy and immunotherapy in urothelial bladder cancer: harnessing the full potential of the anti-tumor immune response

Abstract: Purpose Radiotherapy (RT), as part of trimodal therapy, is an attractive alternative treatment in patients with urothelial muscle-invasive bladder cancer (MIBC). There is accumulating evidence suggesting the immunomodulatory effects of RT and its potential synergy when combined with immunotherapy. The aim of this review was to report on the most recent advances on this combination, including the mechanisms of RT immunomodulation, practical approach to combining RT and immunotherapy, and ongoing clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Dovedi et al reported that mice treated with anti–PD-L1 treatment and concurrent irradiation had longer survivals compared to those treated with anti–PD-L1 treatment seven days after irradiation in vivo [ 28 ]. However, the concurrent use strategy may not be clinically feasible because previous clinical trials were discontinued due to unacceptably high rates of severe adverse events following the concurrent use of hypofractionated radiotherapy and anti–PD-1/PD-L1 treatment in UC patients [ 29 , 30 ]. Meanwhile, recent findings from clinical data, including ours, showed that a history of radiotherapy was significantly associated with favorable prognosis after pembrolizumab therapy in patients with advanced UC [ 31 ] and non-small cell lung cancer [ 32 ], in which a history of radiotherapy was not associated with higher rates of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Dovedi et al reported that mice treated with anti–PD-L1 treatment and concurrent irradiation had longer survivals compared to those treated with anti–PD-L1 treatment seven days after irradiation in vivo [ 28 ]. However, the concurrent use strategy may not be clinically feasible because previous clinical trials were discontinued due to unacceptably high rates of severe adverse events following the concurrent use of hypofractionated radiotherapy and anti–PD-1/PD-L1 treatment in UC patients [ 29 , 30 ]. Meanwhile, recent findings from clinical data, including ours, showed that a history of radiotherapy was significantly associated with favorable prognosis after pembrolizumab therapy in patients with advanced UC [ 31 ] and non-small cell lung cancer [ 32 ], in which a history of radiotherapy was not associated with higher rates of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy targeting the PD-1/PD-L1 pathway has had good effects in treating urothelial tumors (27). It has been reported that radiotherapy has the potential to synergize with immunotherapy to improve oncological outcomes in patients with urothelial muscle-invasive bladder cancer (28). PD-L1 expression on tumor cells independently predicted shorter CSS in UTUC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Given this volume is up to 45% smaller than an anatomically defined bladder GTV, it opens the possibility of further normal tissue sparing (131). As the volume of radiation influences the immunogenic potential of the tumor microenvironment, defining alternative meaningful target sub-volumes particularly with systemic immunotherapy warrants further evaluation (132,133).…”
Section: Beyond Geometric Adaptionmentioning
confidence: 99%